Design and fabrication of automatic waffle dry ingredients mixer / Iskandar Zulkarnain Zamri - Zamri, Iskandar Zulkarnain (2024)
Waffles are among the most sought-after foods, especially during teatime. However, to make waffles need time to measure and mix ingredients. Addition, a lot of people don’t know the ingredients of making waffle. With this automatic waffle dry ingredients mixer will reduce time taken for measuring the quantities of waffle batter without the need for manual work and it will mix it well at the end of the process. The market for this product also includes restaurants, cafes, hotels, and other foodservices establishments that serve waffles in their menu, it is not for kitchen use only. So, the marketplaces for this product will achieve the maximum demand.